Development of a database of kazakhstani digital multicultural content as a means of training future journalists: Astana IT University, Kazakhstan, Astana city (Herald of Journalism, 2022)
This article presents the practice of analyzing digital multicultural content and its application in the classes with students from the educational programs: “Digital Journalism” and “Media Technologies”. The choice of the topic is explained by the specifics of the cultural code of the modern student. The purpose of the paper is to study digital multicultural content as a mean of training future media workers using modern IT tools.The article examines the multicultural content of three TV channels and online publications hosted on digital services. The design and structuring of web portals, interface and content are studied. Due to the specifics of the subject of multicultural content, its role in the general information space is determined, and its relevance and relevance among students is described. The author conducts quantitative and qualitative researches of media materials. Based on statistical data, a comparative analysis of the indicators of digital multicultural content for 2018-2021 was carried out and the dynamics was demonstrated, the reasons for the change in indicators were described in detail. A parallel is drawn between the amount of digital content published on television and on Internet resources. Considering the need to prepare students for professional realities and for the purpose of practical orientation of this research, a lexical and compositional analysis of digital multicultural content was carried out. In particular, the study examined genres and forms of materials, lexical features of texts. The means of social interaction of online media representations are defined, which include the constant presentation of traditional media content in a virtual environment and monitoring of activity in the classroom. The structural and typological features of this format of digital journalism are revealed. Based on a qualitative analysis of the content, several trends and conclusions are presented.The information obtained during the study was organized into a database. The methods of working with students described and analyzed in this article are an important material for the development of educational goals of the educational programs “Digital Journalism” and “Media Technologies” in Kazakhstan and can become a methodological basis for the integration of IT technologies into media education.Key words: multicultural content, content analysis, journalistic education, format, media technologies, digital journalism, databases, training means.